Effect of microbial consortium on plant growth and improvement of alkaloid content in Withania somnifera (Ashwagandha) - R. Elango, S. Rajasekar* and (Current Botany, 2011)
The effect of microbial consortium consisting Plant Growth Promoting Rhizobacteria (PGPR) like Azospirillum, Azotobacter, Pseudomonas and Bacillus were tested separately and in combination on Withania somnifera for two consecutive years (2009 and 2010). The combinations of above mentioned PGPR strains significantly increased plant height, root length, and alkaloid content in Withania somnifera when compared to the uninoculated control. Plant growth promoting rhizobacteria (PGPR) exhibit direct and indirect mechanisms as plant growth promoters and biological control agents. Direct mechanism by PGPR, include the provision of bio-available phosphorus for plant uptake, nitrogen fixation for plant. The results of this study suggest that the PGPR applied in combination have the potential to increase the plant growth, alkaloid content of Withania somnifera.